Data Warehouse: Analysis into its Evolution, Benefits and Pitfalls - Cheah, Darren Yao Chun (2008)
The purpose of this thesis is to investigate the benefits and advantage of a data warehouse when applied to several industries, that being the banking and finance, retail, travel and manufacturing industries. The author will discuss the evolution of usage of the data warehouse. The author will also investigate the reasons for which a data warehouse project can fail and the disadvantages and potential pitfalls of the data warehouse